Synaptic endocytosis: illuminating the role of clathrin assembly. - Rodal, A.A.; Littleton, J.T. (Current Biology, 2008)
Acute photo-inactivation of clathrin in Drosophila synapses sheds new light on a 35-year-old debate over mechanisms of synaptic-vesicle endocytosis: clathrin is essential for reformation of functional synaptic vesicles, but not for bulk membrane internalization.